A Short Form of the Children's Experiences of Dental Anxiety Measure (CEDAM): Validation and Evaluation of the CEDAM-8 - Jenny Marie Porritt; Annie Morgan; Helen Rodd; Fiona Gilchrist; Sarah R. Baker; Tim Newton; Zoe Marshman (MDPI AG, 2021)
Background: The Children's Experiences of Dental Anxiety Measure (CEDAM-14) is a child-centred measure of dental anxiety which assesses a range of behaviours, thoughts and feelings/physical symptoms related to dental anxiety. A short form of the CEDAM-14, which places less time burden on patients and clinicians, could promote the feasibility and applicability of the CEDAM in clinical settings. The aim of the study was to develop a short version of the CEDAM that can be used to assess children's dental anxiety in clinical practice. Methods: A short version of the CEDAM was developed using a combination of item impact and regression methods. Measurement properties including floor/ceiling effects, variance, criterion validity, construct validity and internal consistency was calculated for the short form. Results: An eight-item CEDAM short form was developed (CEDAM-8) that had good psychometric properties, was significantly correlated with the CEDAM measure (r = 0.90; p < 0.01), had minimal floor and ceiling effects (3.5% and 1.2%, respectively) and was sensitive to change. Conclusion: The CEDAM-8 is a useful assessment tool for clinicians that is easy and quick to administer and could help to understand children's experiences of dental anxiety and changes in anxiety over time and following intervention.